Globalisasi dan Kemiskinan - Effendi, Tadjudin Nur (Jurnal Ilmu Sosial dan Ilmu Politik, 2003)
Globalization, namely integration of the world economy into a single market, has been unprecedently affecting every part of the world as technological development has allowed handful bussines effectively control local resourcess. Properity and advantages brought about by globalization, however, is not equally shared, as investment, growth and modern technologies are concentrated mainly in the developed countries. Moreover, developing countries including Indonesia are not only deprived but also excluded from it. Analysis of recent history in Indonesia presented in this article shows that integration into global market even created a deindustrialization process to take place. The level of unemployment and proverty is getting worse as Indonesia increasingly more integrated into the world economy.